The Social Challenges of a Working Muslim Women in a Patriotic Society in Indonesia - Dalimoenthe, Ghassaani Arifah (Jurnal Indonesia Sosial Sains, 2025)
In modern nations, women's roles have significantly evolved, granting them increased access to education, employment, and social mobility. Women's equality and autonomy are now often seen as hallmarks of progress, contrasting with traditional frameworks that reinforce male dominance. Despite these advancements, the women’s movement advocating for gender rights continues globally. In developing countries like Indonesia—a Muslim-majority state—the societal view of women's roles remains complex. Many still prioritize marriage over education for women, and traditional values often expect women to be devoted wives and mothers, even as more women enter the workforce. This study explores how Indonesia reconciles traditional Islamic values with modern gender roles, particularly regarding Muslim women in the labor force. Employing qualitative research methods, this study analyzes secondary data from books, scholarly journals, official documents, news articles, and online sources to understand the societal, religious, and political dimensions influencing the participation of Muslim women in Indonesia's workforce. The findings reveal an ongoing negotiation between religious expectations and modern socio-economic demands, showing how Muslim women balance cultural obligations with professional aspirations. This research contributes to discussions on gender, religion, and modernization in Southeast Asia, emphasizing the importance of contextual sensitivity in addressing gender equity.